Contemporary Applications of Ultrasound in Abdominal Aortic Aneurysm Management - Scaife, Mark; Giannakopoulos, Triantafillos; Al-Khoury, Georges E.; Chaer, Rabih A.; Avgerinos, Efthymios D. (Frontiers in Surgery, 2016)
Ultrasound (US) is a well-established screening tool for detection of abdominal aortic aneurysms (AAA) and is currently recommended not only for those with a relevant family history but for all men and high-risk women older than 65 years of age. The advent of minimally invasive endovascular techniques in the treatment of AAAs (EVAR) has increased the need for repeat imaging especially in the post-operative period. Nevertheless, preoperative planning, intraoperative execution and postoperative surveillance all mandate accurate imaging. While CTA and angiography have dominated the field, repeatedly exposing patients to the deleterious effects of cumulative radiation and intravenous nephrotoxic contrast, ultrasound technology has significantly evolved over the past decade. In addition to standard color duplex US, 2D, 3D or 4D contrast enhanced US modalities are revolutionizing AAA management and postoperative surveillance. This technology can accurately measure AAA diameter and volume and most importantly it can detect endoleaks post EVAR with high sensitivity and specificity. 4D contrast enhanced US can even provide hemodynamic information about the branch vessels following fenestrated EVARs. The need for experienced US operators and accredited vascular labs is mandatory to guarantee the reliability of the results. This review article presents a comprehensive overview of the literature on the state-of-art US imaging in AAA management, including post EVAR follow-up, techniques and diagnostic accuracy.